Gender differences in electro-mechanical characteristics of left bundle branch block: Potential implications for selection and response of cardiac resynchronization therapy. (15th April 2018) - De Pooter, Jan; Kamoen, Victor; El Haddad, Milad; Stroobandt, Roland; De Buyzere, Marc; Jordaens, Luc; Timmermans, Frank
Abstract: Background: Female patients are underrepresented in cardiac resynchronization therapy (CRT) trials, although they show better CRT response compared to males and at shorter QRS durations. We hypothesized that differences in left bundle branch block (LBBB) characteristics and mechanical dyssynchrony might explain this gender disparity. Methods: Patients presenting with true LBBB-morphology (including mid-QRS notching) on surface electrocardiograms (ECG) were selected. LBBB QRS duration (QRSDLBBB ) was measured automatically on the ECG. Left ventricular dimensions were assessed by two-dimensional echocardiography. Mechanical dyssynchrony was assessed by the presence of septal flash (SF) on echocardiography. Results: The study enrolled 1037 patients (428 females). Female LBBB patients had smaller QRSDLBBB compared to male LBBB patients (142 [22]ms versus 156 [24]ms, p  < 0.001). In a multivariate analysis, sex and left ventricular end-diastolic diameter (LVEDD ) were independent predictors of QRSDLBBB . QRSDLBBB can be corrected for sex and LVEDD using a simplified formula: corrected-QRSDLBBB  = QRSDLBBB  + 0.5 × (50 − LVEDD ) − 10 (if male). SF was more prevalent in females compared to males (60% versus 43%, p  < 0.001). Women revealed significantly more SF in narrow QRSDLBBB groups compared to men: 65% versus 13% ( p  < 0.001) with QRSDLBBB 120–129 ms, 66% versus 18% ( p  < 0.001) with QRSDLBBB 130–139 ms and 63% versus 31% (p < 0.001) with QRSDLBBB 140–149 ms. At QRSDLBBB  > 150 ms, there were no differences in SF prevalence between females and males. Conclusion: Female patients show true LBBB morphology at shorter QRSD and have more frequent mechanical dyssynchrony at shorter QRSD compared to males. This might explain the better CRT response rates at shorter QRSD in females.